Implementing gene curation for hereditary cancer susceptibility in Australia: achieving consensus on genes with clinical utility. Issue 12 (9th November 2020) - Tudini, Emma; Davidson, Aimee L; Dressel, Uwe; Andrews, Lesley; Antill, Yoland; Crook, Ashley; Field, Michael; Gattas, Michael; Harris, Rebecca; Kirk, Judy; Pachter, Nicholas; Salmon, Lucinda; et al.
Abstract : Background: The strength of evidence supporting the validity of gene-disease relationships is variable. Hereditary cancer has the additional complexity of low or moderate penetrance for some confirmed disease-associated alleles. Methods: To promote national consistency in interpretation of hereditary cancer/tumour gene test results, we requested opinions of representatives from Australian Family Cancer Clinics regarding the clinical utility of 157 genes initially collated for a national research project. Viewpoints were sought by initial survey, face-to-face workshop and follow-up survey. Subsequent review was undertaken by the eviQ Cancer Genetics Reference Committee, a national resource providing evidence-based and consensus-driven cancer treatment protocols. Results: Genes were categorised by clinical actionability as: relevant for testing on presentation of common cancer/tumour types (n=45); relevant for testing in the context of specific rare phenotypes (n=74); insufficient clinical utility (n=34) or contentious clinical utility (n=3). Opinions for several genes altered during the study time frame, due to new information. Conclusion: Through an iterative process, consensus was achieved on genes with clinical utility for hereditary cancer/tumour conditions in the Australian setting. This study highlighted need for regular review of gene-disease lists, a role assumed in Australia for hereditary cancer/tumour predisposition genes by the eviQ Cancer Genetics Reference Committee.